2013
DOI: 10.1186/2008-2231-21-28
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of silyamarin in individuals chronically exposed to hydrogen sulfide; modulating influence of TNF-α cytokine genetic polymorphism

Abstract: Background and the purpose of the studySilymarin, a standardized extract of the milk thistle (Silybum marianum), is believed to exert some of its hepatoprotective effects though inhibition of free radicals and inflammation. In this study the effect of some pro- and anti-inflammatory cytokines and also antioxidant genes polymorphisms on the hepatoprotective effects of silymarin in the occupationally exposed individuals to hydrogen sulfide (H2S) in the sour natural gas refinery was investigated.MethodsWe genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Silymarin has been shown to resist hepatocyte and cardiomyocyte apoptosis (4,7,18). The results from this study also confirmed that CCl 4 -induced liver fibrosis in rat hearts indeed utilized the FAS-L/FAS/ FADD-induced death pathway.…”
Section: Discussionsupporting
confidence: 79%
“…Silymarin has been shown to resist hepatocyte and cardiomyocyte apoptosis (4,7,18). The results from this study also confirmed that CCl 4 -induced liver fibrosis in rat hearts indeed utilized the FAS-L/FAS/ FADD-induced death pathway.…”
Section: Discussionsupporting
confidence: 79%
“…This outcome was in agreement with results of other studies that have indicated the antiinflammatory properties of silymarin and its potential for inhibiting the production of pro-inflammatory cytokines such as IL-1β, IL-2 and INF-γ through the suppression of various inflammatory pathways (Manna et al 1999;Gharagozlooa et al 2010). Previously, the anti-inflammatory characteristics and probable underlying mechanisms of silymarin had been demonstrated in cell line studies (Kang et al 2004;Mandegary et al 2013), which may explain the changes of hs-CRP levels observed in our study. It has been claimed that silymarin can inhibit the formation of 5-lypoxiganase products including lukotrienes and also inhibit enzymatic peroxidation in the lipoxygenase and cyclooxygenase pathways involved in inflammation (Gupta et al 1999;Alarcon et al 1992).…”
Section: Discussionmentioning
confidence: 42%
“…Silymarin (SM), is a polyphenolic flavonoid derived from the seeds and fruits of the milk thistle plant ( Silybum marianum ), routinely used to treat liver diseases and have antioxidative [ 17 ], anti-apoptotic [ 18 ], anti-inflammatory [ 19 , 20 ], and neuroprotective properties [ 21 ]. The anti-oxidative activity of SM is due to the scavenging of free radicals and activation of superoxide dismutase [ 22 ].…”
Section: Introductionmentioning
confidence: 99%